STRATEGIC CIRCULAR ECONOMY MANAGEMENT FOR LOW-CARBON URBAN WASTE GOVERNANCE (POLITEKNIK LP3I JAKARTA, 2026)
The growing volume of municipal solid waste and increasing greenhouse gas (GHG) emissions have made effective urban waste governance a critical component of sustainable development. Although circular economy initiatives have gained global attention, research has largely focused on technological solutions and resource efficiency, with less emphasis on the governance capacity needed to ensure successful implementation. This study examines how governance capacity supports circular economy implementation in advancing Sustainable Development Goal (SDG) 12 and climate mitigation through sustainable urban waste management in Jakarta, Indonesia. Using a qualitative case study approach, the research applies the Context–Input–Process–Product–Outcome (CIPPO) framework, supported by policy analysis, government reports, and relevant literature. The findings show that Jakarta has strengthened its circular economy initiatives through the expansion of waste banks, TPS 3R facilities, refuse-derived fuel (RDF) plants, and waste-to-energy infrastructure. However, fragmented institutional coordination, inconsistent policy implementation, limited stakeholder collaboration, and financing constraints continue to affect their effectiveness. This study proposes an integrated governance framework that highlights governance capacity as the key driver connecting circular economy implementation with greenhouse gas reduction. The framework provides practical insights for strengthening sustainable urban waste governance and accelerating progress toward SDGs 11, 12, 13, and 17, while supporting Indonesia's transition to a low-carbon circular economy.